2015
DOI: 10.1039/c5cp00476d
|View full text |Cite
|
Sign up to set email alerts
|

The microwave heating mechanism of N-(4-methoxybenzyliden)-4-butylaniline in liquid crystalline and isotropic phases as determined using in situ microwave irradiation NMR spectroscopy

Abstract: Microwave heating effects are widely used in the acceleration of organic, polymerization and enzymatic reactions. These effects are primarily caused by the local heating induced by microwave irradiation. However, the detailed molecular mechanisms associated with microwave heating effects on the chemical reactions are not yet well understood. This study investigated the microwave heating effect of N-(4-methoxybenzylidene)-4-butylaniline (MBBA) in liquid crystalline and isotropic phases using in situ microwave i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…We only briefly want to name four examples of how research is progressing to investigate potential specific microwave effects. For example, silicon carbide reactor vials were designed to separate thermal and potential non‐thermal microwave effects, a combination of temperature measurement by an internal fiber probe and an external IR sensor was applied to obtain more‐reliable and reproducible heating profiles, and in situ Raman and NMR spectroscopy were used to investigate the molecular mechanisms associated with microwave‐heating effects on chemical reactions.…”
Section: Fundamentals Of Heating Carbon Materials Using Microwave Irrmentioning
confidence: 99%
“…We only briefly want to name four examples of how research is progressing to investigate potential specific microwave effects. For example, silicon carbide reactor vials were designed to separate thermal and potential non‐thermal microwave effects, a combination of temperature measurement by an internal fiber probe and an external IR sensor was applied to obtain more‐reliable and reproducible heating profiles, and in situ Raman and NMR spectroscopy were used to investigate the molecular mechanisms associated with microwave‐heating effects on chemical reactions.…”
Section: Fundamentals Of Heating Carbon Materials Using Microwave Irrmentioning
confidence: 99%
“…The local dipolar interaction of individual protons in the liquid crystalline state can be examined by this method via high resolution resonance in the isotropic phase, and the resulting data can also be used to obtain state-correlated 2D NMR spectra of proteins in both native and denatured states . In situ microwave irradiation NMR spectroscopy was developed later, and the microwave heating process was observed in liquid crystalline samples. , In the liquid crystalline molecules, the different protons were found to indicate significantly different temperature …”
Section: Introductionmentioning
confidence: 99%
“…30 In situ microwave irradiation NMR spectroscopy was developed later, 31 and the microwave heating process was observed in liquid crystalline samples. 31,32 In the liquid crystalline molecules, the different protons were found to indicate significantly different temperature. 32 Molecular dynamics (MD) simulations have recently been conducted to investigate the atomic-scale properties of molecular systems under an electric field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous 1 H NMR studies of LCs showed distinct differences in the spectra between the various crystalline and isotropic phases . One group detected the LC phase transition from nematic (crystalline) phase to isotropic phase.…”
Section: Theorymentioning
confidence: 99%